Instrument shank-assisted ovariohysterectomy: a randomized clinical trial of surgical and pain alleviation efficiency of a single-person modified technique - Ziaei Darounkolaei, Navid; Mousavi Kiasary, Seyed Mohamad Sadegh; Behzadi, Amirhoushang; Nabavi Mosavi, Niki; Ferdowsi, Shima Mahmoodi (Frontiers in Veterinary Science, 2023)
Objectives: To evaluate a modified ovariohysterectomy (OHE) technique performed by a single person and compare it with the conventional method based on time efficiency, trauma, and postoperative pain. Methods: In a prospective, randomized, experimental study, 18 healthy, large, deep-chested, mixed-breed intact female dogs were randomly allocated to conventional (n = 9) and instrument shank-assisted (n = 9) groups. On the basis of video recordings, the various surgical step durations were analyzed: total surgery time (TST), pedicle intervention time (PIT), suspensory release time (SRT), shanking time (ShT), clamping time (ClpT), ligating time (LigT), and closure time (CT). The Glasgow composite pain scale short-form (GCMPS-SF), university of Melbourne pain scale (UMPS), and Visual Analogue Scales (VAS) were used to measure pain. C-reactive protein (CRP) fluctuation was also investigated. These evaluations were completed before and 6, 24, 48, and 72 hours postoperatively. Results: Instrument shank-assisted OHE was less time-consuming than conventional OHE (p=0.005), improved PIT by 30.7% (6.44 minutes for both pedicles, p=0.014), and correlated strongly with TST (ρ= .862, p=0.003 and ρ= .955, p=0.000, respectively). The two method’s surgical step durations were also TST=47.40±9.9 vs. 34.70±6.7 minutes, PIT=20.96±5.78 vs. 14.52±3.73 minutes, SRT=78.97±69.10 vs. ShT=20.39±8.18 seconds (p=0.035), ClpT=50.66±45.04 vs. 63.55±37.15 seconds (p=0.662), LigT=12.82±3.37 vs. 8.02±3.11 minutes (p=0.005), and CT=16.40±4.5 vs. 11.60±2.5 minutes (p=0.013), respectively. While both techniques inflicted pain on the animals, the novel approach resulted in a reduction of pain at T6 (GCMPS-SF, p=0.015 and VAS, p=0.002), T24 (UMPS, p=0.003), and T48 (GCMPS-SF, p=0.015 and UMPS, p=0.050). Both methods exhibited a peak in CRP level after 24 hours, which subsequently returned to baseline after 48 hours. However, the shank-assisted method demonstrated a significantly lower reduction in CRP level at the 48-hour compared to the other group (p=0.032). Conclusions: Instrument shank-assisted technique permitted ovarian removal without an assistant, less damage to animals and reducing its time when compared to a conventional technique, and resulting in an alternative that causes less surgical stress and fatigue. Further research with a larger population size is required to determine the serum CRP levels as an alternative pain biomarker.